Feasibility Assessment of Micro-Electrode Chip Assay as a Method of Detecting Neurotoxicity in vitro - Defranchi, Enrico; Novellino, Antonio; Whelan, Maurice; Vogel, Sandra; Ramirez, Tzutzuy; Van Ravenzwaay, Ben; Landsiedel, Robert (Frontiers in Neuroengineering, 2011)
Detection and characterization of chemically-induced toxic effects in the nervous system represent a challenge for the hazard assessment of chemicals. In vivo, neurotoxicological assessments exploit the fact that the activity of neurons in the central and peripheral nervous system has functional consequences. And so far, no in vitro method for evaluating the neurotoxic hazard has yet been validated and accepted for regulatory purpose. The microelectrode array (MEA) assay consists of a culture chamber into which an integrated array of microelectrodes is capable of measuring extracellular electrophysiology (spikes and bursts) from electro-active tissues. A wide variety of electrically excitable biological tissues may be placed onto the chips including primary cultures of nervous system tissue. Recordings from this type of in vitro cultured system are non invasive, give label free evaluations and provide a higher throughput than conventional electrophysiological techniques. In this paper, twenty substances were tested in a blinded study for their toxicity and dose-response curves were obtained from foetal rat cortical neuronal networks coupled to MEAs. The experimental procedure consisted of evaluating the firing activity (spiking rate) and modification/reduction in response to chemical administration. Native/reference activity, 30 minutes of activity recording per dilution, plus the recovery points (after 24 hours) were recorded. The preliminary data, using a set of chemicals with different mode-of-actions (13 known to be neurotoxic, 2 non-neuroactive and not toxic and 5 non-neuroactive but toxic) show good predictivity (sensitivity: 0.77; specificity: 0.86; accuracy: 0.85). Thus, the MEA with a neuronal network has the potency to become an effective tool to evaluate the neurotoxicity of substances in vitro.